Oral Hairy Leukoplakia: Clinical Indicator of an Immunosuppressive Condition and Challenges in Patient Management - Agustina, Yohana Alfa; Wardhany, Indriasti Indah; Wimardhani, Yuniardini Septorini; Krisnuhoni, Ening; Iamaroon, Anak (Journal of Dentistry Indonesia, 2016)
Oral hairy leukoplakia (OHL) is defined as an asymptomatic white patch with vertical corrugation pattern the lateral borders of the tongue, that is associated with Epstein-Barr Virus (EBV) infection. Generally, it is related to immunosuppressive condition found in HIV-positive patients and patients undergoing immunosuppressive therapy. Sometimes, its clinical appearances could mimic other white lesions. Although most OHL cases are found in HIV seropositive individuals, finding in the immunocompetent individuals has also been reported. Appropriate clinical evaluations and laboratory investigations are important for patient’s comprehensive management. Objective: To report a finding of oral hairy leukoplakia as a clinical indicator of an immunosuppressive condition in otherwise a clinically healthy-looking individual and to discuss the challenges on patient management. Case Report: A 40 yearold man presented with asymptomatic, bilateral homogenous white hyperkeratotic plaques with a hairy appearance located on the dorsal of the tongue, extended to the lateral tongue mucosa. The patient failed to remember the lesion’s first appearance, until three weeks before a visit. Working diagnosis of OHL was made with differential diagnoses including white sponge nevus, leukoplakia and oral lichen planus. Histopathological assessment was consistent with OHL. Challenges on patient management include identifying possible risk factors and assuring patient for HIV testing. Conclusion: This case reported findings of OHL as the first clinical indicator of immunosuppressive condition that might be related to HIV-infection.